Characteristics of Pavement Cement Concrete Incorporating Steel Slag Powder - Erbu Tian; Yamin Liu; Xianpeng Cheng; Wuhua Zeng (Advances in Materials Science and Engineering)
After thermal braising and magnetic separation, steel slag is often ground into steel slag powder (SSP), which contains active silica (SiO2) and can be used as a cementitious material to replace part of the cement and applied in concrete. However, there have been relatively few studies on the influence of SSP on the performance of pavement cement concrete (PCC). In this paper, SSP was used as an admixture to replace part of the cement in the cement paste, cement mortar, and PCC, to investigate the effect of SSP on the fluidity of SSP-cement slurry, the mechanical properties, and the durability of PCC. Results showed that SSP can lead to the secondary hydration reaction with Ca(OH)2 in the cement paste and affect the hydration products, morphology, pore characteristics, and strength of the cement paste. When the SSP mixing amount was less than 20% and up to 1.3% superplasticizer was added, the fluidity of the cement slurry could be optimized. For the samples with the SSP mixing amount of less than 20%, the concrete compressive strengths were greater than 50 MPa, and the flexural strengths were greater than 5.0 MPa. As the SSP mixing amount increased, concrete displayed a better anticarbonization performance. Finally, using 15% SSP, the best performance in terms of the concrete antipermeability (chloride ion diffusion coefficient and electric flux) and frost resistance was achieved.